Wpływ dotychczasowych strategii dywidendowych na bieżące decyzje o wypłatach dywidend przez spółki giełdowe - Kowerski, Mieczysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the paper, using the micro-macro logit models concept, it is shown that previous dividend strategies have influenced the current dividend decisions made by firms quoted on Warsaw Stock Exchange in the years 1995-2006. The decision to pay dividend in current year by the firm which paid dividend last year (Payer) depends on its specific economic financial situation and market position but does not depend on general economic condition in the country. The decision to pay dividend in current year by the firm which did not pay dividend last year but paid in the previous year (Former Payer) or the firm that has never paid it depends on its specific market position and the macroeconomic situation. During prosperity periods these two groups of firms show higher propensity to pay dividends then during recession periods. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 156-164